PENGEMBANGAN PRODUK TABUNGAN DENGAN AKAD MUDHARABAH MUTHLAQAH DI BANK SYARIAH MANDIRI KCP SILIWANGI CIREBON - Afif Muamar; Uswatun Khasanah; Diki Darmawan (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2019)
This study aims to explain the products in Bank Syariah Mandiri and the mechanism of BSM savings products with the Mudharabah Muthlaqah contract. Therefore, this study uses descriptive qualitative methods. The findings in this study, namely, first, there are three types of Bank Syariah Mandiri products that are still operating, which are fundraising products, financing products (channeling funds), and Bank service products. And second, BSM savings are daily savings using the rupiah currency. This account is based on the mudharabah muthlaqah contract system through the channel, namely opening a savings account, depositing BSM savings can be done in all offices of Bank Syariah Mandiri in accordance with the opening hours of cash, cash withdrawals in the teller's skyline customers must come to the office of Bank Syariah Mandiri, closing the BSM savings account fill out the form provided, and the replacement of the lost savings book can be done by making a letter of loss at the nearest police station then submit it to customer service.Â